‘Justice and Right’: Biblical Ethics and the Regulation of Capitalism - Houston, Walter (De Ethica, 2015)
The Hebrew expression in the Old Testament mishpat u-tsedaqa, conventionally translated ‘justice and righteousness’, has a particular application to the social responsibility of the king. The state, in the person of the king, is seen in the Old Testament as having an obligation to exercise its power on behalf of the most vulnerable. This may be illustrated by the widespread evidence from the ancient Near East of administrative and judicial action undertaken by kings to cancel debts, provide for the release of debt slaves, remit taxes, order the return of distrained property, and so forth. Although the impact of such measures would have been limited, and the tradition is attenuated in later levels of the text, the ideal of the state as the protector of the poor may be applied to the state’s relationship with the modern capitalist economy. It demands that the economy should be regulated to protect the most vulnerable against the impoverishment resulting from its transformation by globalized capitalism. The reality, however, especially in the UK and the US, is that the state colludes with capitalism to increase inequality and deepen poverty.